Identification of the Existence and Type of Microplastic in Code River Fish, Special Region of Yogyakarta - Elita Nurfitriyani Sulistyo; Suphia Rahmawati; Rizqia Amalia Putri; Nolanda Arya; Yolanda Amertha Eryan (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
Microplastics are plastic fragments with size less than 5mm in length, according to the U.S. National Oceanic and Atmospheric Administration (NOAA). Microplastics occur and spread in the environment as a result of plastic pollution. Although further assessment is needed to find the health impact of microplastic exposure to humans, several studies show that microplastic might harm the ocean and aquatic life. Code river is one of the big rivers in Yogyakarta. According to the Regional Environmental Agency of Yogyakarta, Code river was highly polluted by domestic waste and wastewater from the settlement along the river and its tributaries. Therefore, the objectives of this research are to investigate the abundance and characteristic of microplastics in fish from Code River Yogyakarta. Fish samples were collected from the fisherman in the upstream, middle, and downstream areas of Code River from February to May 2019. In the laboratory, the samples were analyzed using Wet Peroxide Oxidation (WPO) method. Fish gills and intestine were oxidized using WPO method followed by density separation for 24 hours. Nikon SMZ445 Stereoscopic Microscope with 35x magnification was used to analyze the shape, color, and total of microplastics. The highest abundance was found in fish samples collected from the upstream area (4.33 particles/gram) compare with the downstream area (3.25 particles/gram). The dominant color is blue, while the dominant type of microplastics is fiber.